Quantification of CO2 uptake of concretes with mineral additions after 10-year natural carbonation. (15th May 2022) - Younsi, Akli; Turcry, Philippe; Aït-Mokhtar, Abdelkarim
Abstract: The CO2 uptake of Portland cement, fly ash and blast furnace slag concrete cylinders was determined after 10-year natural carbonation. The purpose was to provide data to better assess the exchanges of CO2 during the life cycle of structures. The CO2 uptake of cylinders (mass of bound CO2 per unit of surface) was calculated from profiles of CO2 content determined by thermogravimetric and chemical analyses. The CO2 binding capacity of concrete with high slag content was found much lower than that of Portland cement concrete, due to the low degree of carbonation of CaO from slag. The CO2 uptakes of the studied specimens were however rather close. High carbonation depth of slag concretes compensates partly their lower binding capacity. The experimental results were compared to predictions of the European Standard EN 16757 model. The Standard model underestimates the CO2 uptake of concretes with mineral addition mainly because of an underestimation of the carbonation depth.